Analysis of the Performance of Indonesia's Defense Offset Policy and Its Development Strategy Using SWOT Analysis - Permatasari, Harnung Indah; Almubaroq, Hikmat Zakky; Sudarya, Agus (Formosa Journal of Science and Technology, 2024)
The research evaluates the implementation of offset policies in Indonesia's defense sector, focusing on its role in advancing domestic industries and technology transfer. Using a qualitative descriptive approach with SWOT analysis, this study examines secondary data, including global best practices and Indonesia's collaborative efforts with France, Germany, UAE, and Russia. Findings reveal Indonesia's potential in leveraging offsets for industrial growth but highlight regulatory, monitoring, and resource challenges. The study concludes that clear regulations, enhanced R&D investment, and structured offset mechanisms are critical for maximizing benefits. Strategic recommendations include establishing a dedicated offset agency and fostering international partnerships. These insights contribute to academic knowledge and offer actionable strategies for Indonesia's defense and economic resilience.